Back-stepping Adaptive SVM Direct Torque Control of SPMSM Drive system - Hua Sun; Xuan Cui; Chuansheng Tang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A novel back-stepping adaptive control strategy is proposed to direct torque control (DTC) of surface permanent magnet synchronous motor (SPMSM) in order to solve some problems existed in conventional DTC, such as high flux , torque and current ripple, variable switching frequency, and acoustic noises. PI speed regulator and two hysteresis regulators in the conventional DTC system are substituted by the proposed back-stepping adaptive controller respectively. The output of the designed controller makes space vector modulation (SVM) possible, which further ensures the inverter switching frequency to be fixed. The stability of the controller is verified via Lyapunov stable theory.Simulation results show that the presented control strategy can solve these problems effectively and show strong robust to external disturbance and noise.